Effectiveness of Teacher Communication in Improving Student Achievement in MTs. Al-Wasliyah Pulo Brayan Medan, Indonesia - Syahrul Abidin (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2021)
The aims of this study is to find out the Effectiveness of Teacher Communication in Improving Student Achievement in MTs. Al-Wasliyah Pulo Brayan Medan, Indonesia. This study use qualitative research. The result of this study shows that Based on the reality of teacher communication strategies in improving student achievement in MTs. Al-Wasliyah Pulo Brayan Medan can be put forward several conclusions, as follows: 1. The communication strategy that is widely used by teachers is in the form of reward and punishment. In this case the teacher always gives sanctions to students if they make mistakes. The sanctions can be in the form of a pinch, a punch, or also advice. On the other hand, with regard to giving rewards, most teachers rarely give gifts to their students if they excel. 2.The communication strategy carried out by teachers in educating to improve student achievement will work well, if the school, teachers and parents work together in creating harmony. Harmony between teachers, students and parents is realized first. With the harmony between the school and parents, children will feel calm in the teaching and learning process which will later achieve brilliant achievements.